Store-operated Ca2+ entry in muscle physiology and diseases - Pan, Zui (Korean Society for Biochemistry and Molecular Biology, 2014)
Ca2+ release from intracellular stores and influx from extracellular reservoir regulate a wide range of physiological functions including muscle contraction and rhythmic heartbeat. One of the most ubiquitous pathways involved in controlled Ca2+ influx into cells is store-operated Ca2+ entry (SOCE), which is activated by the reduction of Ca2+ concentration in the lumen of endoplasmic or sarcoplasmic reticulum (ER/SR). Although SOCE is pronounced in non-excitable cells, accumulating evidences highlight its presence and important roles in skeletal muscle and heart. Recent discovery of STIM proteins as ER/SR Ca2+ sensors and Orai proteins as Ca2+ channel pore forming unit expedited the mechanistic understanding of this pathway. This review focuses on current advances of SOCE components, regulation and physiologic and pathophysiologic roles in muscles. The specific property and the dysfunction of this pathway in muscle diseases, and new directions for future research in this rapidly growing field are discussed. [BMB Reports 2014; 47(2): 69-79]